Tindak Pidana Korupsi: Tantangan dalam Penegakan dan Pencegahannya - Graciella Nathalie Winata (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Corruption is one of the criminal acts that most damages the social, economic and political order of a country. Corruption has become a crucial problem that hampers national development, affects public trust in government institutions, and reduces the quality of public services. In this context, legal analysis regarding criminal acts of corruption is very important to understand the challenges faced in law enforcement as well as preventive measures that can be implemented. Although there have been various efforts by the government and law enforcement agencies to eradicate corruption, the challenges that arise are often complex and multidimensional. With a holistic approach, various strategic solutions can be explored, including legal reform, strengthening supervisory systems, public education, economic empowerment, and the application of modern technology such as blockchain. Apart from that, the importance of collaboration between government, society, anti-corruption institutions and the private sector is also emphasized to create a transparent and accountable environment. In conclusion, eradicating corruption requires a joint commitment from all elements of society to achieve sustainable and equitable development goals.